(untitled) (International Journal of Engineering and Computer Science, 2016)
The basic ideas involving cloud computing were first came into picture in 1960, when John McCarthy stated that "computation may someday be organized as a public utility". But the concept of Cloud computing started drawing attention of the IT world until recently. It is changing the focus of enterprises. It has become a part of normal work flow for thousands of users on the internet. Cloud computing gained attention due to many of its salient features such as reduced storage cost, ‘pay per use’ policy, the growing technology of visualization, SOA (Service Oriented Architecture) and also because of development in internet security. Cloud security is one of the major challenges in cloud computing. This paper focuses on various cloud security issues and methods to enhance the security of data storage and processing in the clod environment. The definition of cloud computing and some of its features are also discussed in this paper.